Centennial dynamics of stocks and average individual weight for pacific salmon in the Russian Far East through the prism of climate cycles and trends - E. A. Shevlyakov; V. I. Ostrovsky (Известия ТИНРО, 2025)
Complex nature of long-term dynamics is revealed for thermal parameters of the pacific salmon habitat that includes a trend to warming and cyclic changes. Changes in annual landing of pink, chum and sockeye salmon have generally positive relationship to variations of the temperature background. Period of a full cycle in the dynamics of pink, chum, sockeye, coho, and chinook salmon abundance is about 80 years, with the cycles for pink, chum and sockeye salmon synchronous to those of temperature, the cycles for chinook salmon counter-phase them, and the variations in coho salmon abundance ahead those for pink, chum and sockeye salmon in 20–25 years and ahead those for chinook salmon in ~15 years. In the current cycle, the highest catches of mass species, as pink, chum and sockeye salmon, have been supposedly passed in the early 2020s, so the total annual catch of pacific salmon in Russia is expected to decline to the minimum in 2050s that would be higher than the previous minimum and provide a level of ~250 . 103 t. The individual weight of pacific salmon has a tendency to decrease in the modern times of warming climate. The loss of weight in the last 70–100 years is estimated in 60 % for chinook salmon and 30–35 % for chum, sockeye and coho salmon. Dynamics of the average individual weight for pink salmon is not determined by changes in environments, but depends on abundance of feeding individuals, especially for super-strong year-classes.